People Analytics: análise de dados para a gestão de pessoas por organizações brasileiras - Suda, Paula Massako Bernardes (2021)
As technology advances and promotes transformations, organizations need to be prepared to adapt its strategies and to face up to the various risks these changes may bring to human resource management functions. In this context, although People Analytics is a field in development, its use can help organizations and has been attaining progressively more prominence and presence in nowadays’ debate agenda. Besides other reasons, the small quantity of Brazilian studies related to the topic in ISI Web of Science’s database leads to the key subject of this research: how Brazilian organizations use data analysis in People Management? Therefore, this research aims to collect data on the use of People Analytics through the identification of its main characteristics, applications, advantages and challenges. In order to enable this study, interviews with leaders of these initiatives in Brazilian organizations were carried out, followed by a qualitative data analysis based on Grounded Theory using ATLAS.ti v.9 software. Among this research’s findings, the prevalence of descriptive analytics is visible, but so is of predictive Analytics such as Survival Analysis and ONA (Organizational Network Analysis). The primary focus of People Analytics teams is typically oriented to observe employee turnover, but also to analyze collaboration between coworkers and to be a subsidy of Performance Appraisal processes. The leading challenges are the incessant search for building a foundation of high-quality and availability data, connect originally siloed systems, overcome the skepticism in relation to data-driven decision-making and the lack of analytical skills regarding the professionals involved. The outcomes of this study reveal to organizations that seek to implement or evolve in this matter valuable insights; as for the academics, they provide characteristics of business environment in which People Analytics is applied and unveil knowledge and ability needs that the academics can assist to fill in, fostering transformative praxis